Exchange Rate Devaluation, Interest Rate Volatility, and Investment Growth: ECOWAS Evidence - David Umoru; Rafat Hussaini (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
There are monetary policies and shocks that emanates from adjustments over identified periods that could sway growth rates of investment. The study aimed at determining effect of exchange rate devaluation and interest rate volatility on investment growth in selected ECOWAS nations. We estimated SVAR model in order to identify the influence of policy shocks in exchange rate devaluation and interest rate volatility. The SVAR results revealed that investment growth responds to shocks from exchange rate devaluation negatively at first, but stabilises over time. For interest rate volatility, investment rate continues to grow but at a diminishing rate over the periods. Investment growth was also found to react largely to its internal shocks from its values in lagged periods. The study recommended among others, that devaluation of currency should be implemented as a last resort under sufficient conditions to salvaging ailing ECOWAS economies to sustain current investment growth.